Tissue Culture of Stevia (Stevia rebaudiana Bert.) with the Addition of Aloe vera Extract (Aloe vera (L). Burm.f) on Murashige and Skoog Medium (MS) - Ihsani, Nisa; Nurfitriani, Astri; Kurniasari, Astrid; Tardiansah, Dede Tedi; Rudi, Rudi (AGRIUM: Jurnal Ilmu Pertanian, 2025)
The increasing demand for natural, low-calorie sweeteners highlights the importance of Stevia rebaudiana Bertoni, which produces steviol glycosides that are sweeter than cane sugar and provide health benefits. Due to low seed viability, tissue culture is preferred for propagation, with its success dependent on growth regulators and nutrient availability. Additionally, incorporating plant-derived supplements like Aloe vera, rich in bioactive growth-promoting compounds, may enhance in vitro development. This study aimed to identify the optimal concentration of Aloe vera extract in Murashige and Skoog (MS) medium to enhance the in vitro growth of Stevia rebaudiana. The experiment was conducted using sterile culture bottles arranged in a Completely Randomized Design (CRD) with one experimental factor, namely Aloe vera extract concentration, consisting of five treatment levels: 0%, 5%, 10%, 15%, and 20%. Each treatment was replicated five times, resulting in a total of 25 culture bottles used in this study. Observations were carried out periodically based on several parameters, including shoot, root, stem, and leaf development, as well as overall plant viability and growth performance. The findings demonstrated that 10% Aloe vera extract was the most effective concentration for promoting shoot, stem, and leaf growth, while root growth showed no significant variation across treatments.